Avaliação colostral de cabras acometidas por mastite e sua influ~encia nos níveis imunes séricos de cabrito: Jefferson Filgueira Alcindo. - - Alcindo, Jefferson Filgueira [UNESP] (2014)
The objective of this work was in addition to avaluate the occurrence of mastitis in goats in the postpartum period as well as monitor the quality and colostral transfer of immunity to goats that ingested colostrum and milk of goats suffering from mastitis. Colostrum and blood samples were collected immediately after delivery, 24 and 48 hours after delivery / birth. Physical examination of the mammary glands and the macroscopic evaluation of mammary secretions were also performed at these times. The presence of mastitis in this period was low (16.90%), and the most prevalent form was asymptomatic. The coagulase negative staphylococcus (CNS) were present in most isolations performed (11/12). Physical examination of mammary glands revealed no major changes over the periods evaluated, however the test of CMT (California Mastitis Test) was effective for the diagnosis of asymptomatic mastitis in the immediate postpartum period. The somatic cell count was higher in the positive lactocultura animals when compared to those who had a negative result on this test. There was no difference between the concentrations of IgG in whey after calving between animals with and without mastitis, however the levels of lactoferrin and albumin were increased secretions in the positive microbiological examination compared to samples without isolation. The kids fed colostrum and milk of goats with and without mastitis, showed no failure of transfer of immunity, as evidenced by concentrations of IgG found. The other protein fractions evaluated, did not differ between goats fed or not fed colostrum and mastitic milk over the periods evaluated